Lead, Cadmium, and Arsenic in Edible Tissues of Guinea Pigs Raised in the Central Andes of Peru: Potential Human Health Risk? - Doris Chirinos-Peinado; Jorge Castro-Bedriñana; Fiorela Rivera-Parco; Elva Ríos-Ríos (Veterinary Sciences)
Toxic metals and metalloids food contamination is a source of health risks; this study evaluated lead (Pb), cadmium (Cd), and arsenic (AS) contamination in the meat, liver, kidneys, heart, and lungs of guinea pigs raised on a farm near a mini mineral concentrator and with pastures irrigated with wastewater in the Central Andes of Peru. The risk of consuming these elements was estimated in the Peruvian population aged 2 to 85 years, whose consumption is 660 g/per capita/year. The quantification of Pb, Cd, and As was carried out via Inductively Coupled Plasma Atomic Emission Spectrometry. The heart had 3.3, 4.3, 7.3, and 81 times more Pb than the liver, lung, kidneys, and meat. The liver had 1.02, 2.22, 9.15, and 722.5 times more Cd than the kidneys, heart, lungs, and meat, respectively. The kidneys had 1.16 and 1.72 times more As than the liver and heart, respectively. The Target Hazard Quotient (TQH) and Hazard Index (HI) for Pb, Cd, and As, were <1 in the entire population, and there was no risk from their consumption. The cancer risk values found in the study are within the tolerated ranges. The findings expand the scientific basis for the safe and innocuous production of guinea pigs in the Central Andes of Peru and provide evidence to establish limits on water, soil, pastures, and agri-food products.